Production and processing of rattan - Ngo-Samnick, E. Lionelle (Technical Centre for Agricultural and Rural Cooperation, 2012)
Due to its rapid growth and ability to adapt to a wide variety of ecological conditions, rattan provides a valuable crop that can be grown and harvested in a sustainable manner. Its use in furniture production also means that effective rattan cultivation serves as a reliable alternative to timber exploitation. Clearly laid out and illustrated throughout, this technical guide gives a general overview of the cultivation, harvesting, treatments, transformation and commercilalisation of rattan.